Heat and water flux modeling in an earth dam - Sushant Kumar (IWA Publishing, 2021)
This study aims to identify the water flux in an earth dam using heat flux due to convection. Sixteen earth dam models were constructed in a hydraulic flume by varying geometrical and flow input parameters to identify heat and water flux. Homogeneous as well as earth dams with clay cores were built in a hydraulic flume. Temperature measurements were done to calculate heat flux in the experimental model. A finite element model of the earth dam using Seep/w was developed to obtain water flux, while temp/w was used to obtain heat flux. These results were used as input in Temp/w and Seep/w in Geostudio 2020. Significant reduction of the heat and water flux was seen while comparing the homogeneous models with central impervious core models. An increase in the heat and water flux was observed on increasing the downstream filter's length, longitudinal slope, and vice versa with the upstream slope and the thickness of the clay core. Comparing fluxes in a homogeneous dam model (model 1) with the clay core model (model 9) with top width 2.4 m and bottom width 18 m in model 9, both water flux and heat flux were reduced by 78.46%. While comparing it with model 10, with bottom core width of 18 m and top core width of 1.9 m, both water flux and heat flux reduced by 77.72%. Heat flux measurements were found to be a valuable alternative to detecting water flux and seepage in an earth dam at a reduced cost. HIGHLIGHTS This study identifies the heat due to the convective heat transfer in the respective earth dam model and water flux due to seepage in a porous media such as earth dams by varying geometrical and flow input parameters.; A finite element model using Seep/w was used to determine the water flux, and Temp/w was used to obtain heat flux.; It was observed that near walls of a hydraulic flume, soil pores of the earth dam were of larger volume, resulting in an increased local water flow.; Increased heat and water fluxes were observed when the downstream filter length and longitudinal slope were increased, and vice versa with the upstream slope and thickness of the clay core.; Heat flux obtained was a practical alternative in detecting seepage and water flux in an earth dam.;